Evaluation on combustion and lean-burn limit of a medium compression ratio hydrogen/methanol dual-injection spark-ignition engine under methanol late-injection. (1st November 2020) - Gong, Changming; Li, Zhaohui; Sun, Jingzhen; Liu, Fenghua
Highlights: Combustion of hydrogen/methanol dual-injection engines was studied under lean-burn. Lean-burn limit was compared under different hydrogen addition ratios. Ignition timing was optimized for different hydrogen addition ratios under lean-burn. Hydrogen-enriched could expand the lean-burn limit to excess air ratio 2.95. The critical hydrogen addition ratio for hydrogen-assisted combustion was ≤ 6%. Abstract: Lean-burn is an effective way to optimize the fuel economy of spark-ignition methanol engines. Hydrogen-assisted combustion can improve the stability of combustion and increase the lean-burn limit of such engines. In this study, a medium compression ratio of port injection-type hydrogen/direct-injection methanol was used in a dual-injection spark-ignition engine to investigate the combustion and lean-burn limit under different ratios of addition of hydrogen, excess air ratios, and ignition timings based on methanol late-injection. The results show that the timing of ignition of the hydrogen-enriched methanol engine could be retarded without worsening combustion to a greater extent compared with that in the methanol engine. The timing of ignition had little effect on the coefficient of variation of the indicated mean effective pressure after the addition of hydrogen under lean-burn conditions. Its addition increased the lean-burn limit. The greater the amount of hydrogen added was, the higher the lean-burn limit was. The influence of excess air ratio on the parameters of combustion for 9% of added hydrogen was much smaller than that without hydrogen addition. The critical hydrogen addition ratio from "hydrogen-assisted combustion" to "dual-fuel combustion" was 6%.The optimal ignition timing corresponding to the lean-burn limit at different ratios of added hydrogen was in the range of 33°–42° of the crank angle before the top dead center. Thus, hydrogen-assisted combustion can significantly improve the stability of combustion and increase the lean-burn limit to an excess air ratio of approximately three in a direct-injection spark-ignition methanol engine with a medium compression ratio.